STUDENTS’ PERCEPTIONS OF IMPLEMENTATION MERDEKA CURRICULUM IN SENIOR HIGH SCHOOL - Perangin Angin, Laili Rahma Dewi; Endang Mastuti Rahayu (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2024)
This research was conducted because students have not been able to utilize The Merdeka Curriculum optimally, this is due to the lack of information that students know about The Merdeka Curriculum. The Merdeka Curriculum Program is an important topic in the development of education in Indonesia. Meanwhile, the benefits and challenges of implementing this program continue. From the statement above, researcher interested in knowing students' perceptions of what they felt, especially regarding the benefits and challenges of this curriculum. This study used a qualitative method. This research used data collection took the form of audio recordings of interviews which were then transcribed. The resource data in this research were class XI consist of 5 students for the 2022/2023 academic year. To analyze the data, researcher used thematic analysis. Researcher used content validity to support research. The research results showed that the Merdeka Curriculum made students more motivated in learning, because the Merdeka Curriculum supported students to determine what they want to prepare for in the future, this is also done in choosing elective subjects that they choose according to their interests. The Merdeka Curriculum challenges students to continue to develop and learn new things in order to be able to keep up with the times. Researcher also hope that this research can be a reference for readers to improve the curriculum in the future so that it is better and of better quality for students. and teachers also continue to guide students, and students must be more active in studying.